Concept of INS/GPS integration algorithm designed for MEMS based navigation platform - Tomaszewski, Dariusz (International Conference “Environmental Engineering”, 2017)
Nowadays, along with the advancement of technology one can notice the rapid development of various types of navigation systems. So far, the most popular satellite navigation, is now supported by positioning results calculated with the use of other measurement system. The method and manner of integration will depend directly on the destination of developed system. To increase the frequency of readings and improve the operation of outdoor navigation systems, one can support satellite navigation systems (GPS, GLONASS ect.) with inertial navigation (INS/GPS systems). For the last two decades, due to the miniaturization in electronics it is possible to build GPS/INS systems with the use of low cost MEMS devices. The following study presents the concept of Kalman filter based integration algorithm designed for cheap micro – electronic navigation platform. The tests of considered algorithm were made with the use of MEMS smartphone sensors. Subsequently the results of the study were analyzed to determine the accuracy of featured algorithm.